Cães e gatos: expressão das lesões em intoxicações criminais - Tremori, Tália Missen [UNESP] (2015)
The cases of poisoning no intentional or intentional are common in the history of the Veterinary Medicine mainly in animals of company as dogs and cats. The Legal Veterinary Medicine use these tools in the base of technical decisions to aid processes, involving crimes with animals. According to the Law of Environmental Crimes 9.605 of February 12 of 1998, poisoning in animals is considered crime of mistreatments. The appropriate recognition of the clinical signs, lesions anatomical pathological that characterizes the cases of intoxication that take to death associated with the methods of identification laboratorial of forensic toxicology is fundamental to establish a definitive diagnosis of the toxic agent. In the present work was made analysis of lesions relation of toxic agents and context of Veterinary Forensic Medicine in these situations. In period 2009 to 2014 are selected from the archive of Faculdade de Medicina Veterinária e Zootecnia, UNESP - Universidade Estadual Paulista, Campus de Botucatu, Departamento de Clínica Veterinária, Serviço de Patologia Veterinária 42 cases, 31 (73,8%) dogs and 11 (26,2%) cats. These cases 21 (50%) feature Boletim de Ocorrência and 22 (52,4%) are made toxicologycal exam. The highest prevalence ware intoxication for carbamate. The necropsy revealed that main causa mortis were cardiac respiratory insufficiency and hypovolemic shock. In histopathology of liver, kidney and brain the main lesions are congestion, degeneration and bledding. The organs show signs of autolysis and putrefaction. The diagnostic technics used are additional and help veterinarion to make reports for litigation in cases of criminal intoxication